2019
DOI: 10.1108/md-10-2018-1119
|View full text |Cite
|
Sign up to set email alerts
|

Differential moderating effects of collectivistic and power distance orientations on the effectiveness of work motivators

Abstract: Purpose The purpose of this paper is to investigate the moderating effects of power distance and collectivistic orientations on the effectiveness of intrinsic, extrinsic and reciprocal motivators in promoting employees’ willingness to cooperate for organizational interest. An integrated theoretical framework which incorporated cultural influence on need priority and on legitimacy of social exchange was established to develop the hypotheses. Design/methodology/approach This study used the methodology of infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 85 publications
0
28
0
Order By: Relevance
“…They are unlikely to respond to pandemic threats by trying to bring different viewpoints and solutions into the open. Their subsequent creativity then tends to be lower (Jehn & Bendersky, 2003;Yang, 2019). Taken together, these results offer valuable insights into how and when employees' preoccupations with the COVID-19 pandemic and its impacts might enhance their work behaviors.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…They are unlikely to respond to pandemic threats by trying to bring different viewpoints and solutions into the open. Their subsequent creativity then tends to be lower (Jehn & Bendersky, 2003;Yang, 2019). Taken together, these results offer valuable insights into how and when employees' preoccupations with the COVID-19 pandemic and its impacts might enhance their work behaviors.…”
Section: Discussionmentioning
confidence: 79%
“…They are unlikely to respond to pandemic threats by trying to bring different viewpoints and solutions into the open. Their subsequent creativity then tends to be lower ( Jehn & Bendersky, 2003 ; Yang, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Farh et al (2007) and Newman and Butler (2014) found evidence that the impact of perceived organizational support on employee outcomes is stronger for people scoring low in power distance. Similarly, Yang (2020) found that the effectiveness of intrinsic motivators on employees' willingness to cooperate is stronger for employees who are low in power distance. We therefore expect that the influence of perceived service climate on employee BCB will be stronger for those scores low in power distance orientation.…”
Section: Development Of Hypothesesmentioning
confidence: 93%
“…Yet the reported post hoc analytical results also indicate the clear need for multicountry comparisons that explicitly investigate the effects of pertinent cultural features, such as power distance or collectivism, in terms of (1) how employees react to adverse leadership situations and (2) how relevant personality traits inform these reactions. In a related vein, it would be interesting to examine the roles of corresponding individual values in this process, such as employees' own power distance and collective orientations (Yang, 2019).…”
Section: Limitations and Further Researchmentioning
confidence: 99%